The Modified Coupled Hirota Equation: Riemann-Hilbert Approach and N-Soliton Solutions - Siqi Xu (Abstract and Applied Analysis)
The Cauchy initial value problem of the modified coupled Hirota equation is studied in the framework of Riemann-Hilbert approach. The N-soliton solutions are given in a compact form as a ratio of (N+1)×(N+1) determinant and N×N determinant, and the dynamical behaviors of the single-soliton solution are displayed graphically.